Differential Effects of Iron, Zinc, and Copper on Dictyostelium discoideum Cell Growth and Resistance to Legionella pneumophila - Buracco, Simona; Peracino, Barbara; Andreini, Claudia; Bracco, Enrico; Bozzaro, Salvatore (Frontiers in Cellular and Infection Microbiology, 2018)
Iron, zinc and copper play fundamental roles in eucaryotes and procaryotes, and their bioavailability regulates host-pathogen interactions. For intracellular pathogens, the source of metals is the cytoplasm of the host, which in turn manipulates intracellular metal traffic following pathogen recognition. It is established that iron is withheld from the pathogen-containing vacuole, whereas for copper and zinc the evidence is unclear. Most infection studies in mammals have concentrated on effects of metal deficiency/overloading at organismal level. Thus, zinc deficiency or supplementation correlate with high risk of respiratory tract infection or recovery from severe infection, respectively. Iron, zinc and copper deficiency or overload affects lymphocyte proliferation/maturation, and thus the adaptive immune response. Whether they regulate innate immunity at macrophage level is open, except for iron. The early identification in a mouse mutant susceptible to mycobacterial infection of the iron transporter Nramp1 allowed dissecting Nramp1 role in phagocytes, from the social amoeba Dictyostelium to macrophages. Nramp1 regulates iron efflux from the phagosomes, thus starving pathogenic bacteria for iron. Similar studies for zinc or copper are scant, due to the large number of copper and zinc transporters. In Dictyostelium, zinc and copper transporters include 11 and 6 members, respectively. To assess the role of zinc or copper in Dictyostelium, cells were grown under conditions of metal depletion or excess and tested for resistance to Legionella pneumophila infection. Iron shortage or overload inhibited Dictyostelium cell growth within few generations. Surprisingly, zinc or copper depletion failed to affect growth. Zinc or copper overloading inhibited cell growth at, respectively, 50- or 500-fold the physiological concentration, suggesting very efficient control of their homeostasis, as confirmed by Inductively Coupled Plasma Mass Spectrometry quantification of cellular metals. Legionella infection was inhibited or enhanced in cells grown under iron shortage or overload, respectively, confirming a major role for iron in controlling resistance to pathogens. In contrast, zinc and copper depletion or excess during growth did not affect Legionella infection. Using Zinpyr-1 as fluorescent sensor, we show that zinc accumulates in endo-lysosomal vesicles, including phagosomes, and the contractile vacuole. Furthermore, we provide evidence for permeabilization of the Legionella-containing vacuole during bacterial proliferation.